PATTERN AND FREQUENCY RECONFIGURABLE ANTENNA FOR BODY AREA NETWORK (BAN) (Jurnal Teknologi (Sciences & Engineering), 2015)
A new concept of antenna which quantifies the potential gain of pattern and frequency control in order to suit the requirements of wireless applications such as body area network is presented in this paper. The proposed antenna ranges from 3 GHz to 6 GHz for a wideband operation and operates at 3.5 GHz for a narrowband operation. It uses two types of feedings (CPW and Slotlines) for pattern control with integrated ring resonators for the switching of wideband operation to narrowband operation while maintaining the polarization. The upright return loss characteristics, the controlled radiation pattern and great bandwidth demonstrated at the resonant frequencies make this antenna suitable for applications in these fields.Â Â